The Stake in Adoption of the New Offshore Law: Unlocking Investments in the Black Sea - Cornelia NEAGU; Marius BULEARCĂ; Cristian SIMA; Daniel FISTUNG (Communications of International Proceedings, 2025)
This article deals with a very controversial topic of recent times, namely the need to urgently start the exploitation of hydrocarbon reserves in the Black Sea continental shelf, and the benefits that the Romanian state can obtain from these operations. As a result of the adoption of new regulations regarding the exploitation of natural gas in the Black Sea, more favorable than the previous ones, it seems that investments for the effective start of exploitation have been unlocked, with benefits on multiple levels. For this purpose, the first part of the article highlights that the solution to the energy price crisis is to increase domestic production, including by amending the Offshore Law and unblocking natural gas projects in the Black Sea. As such, the state will have enough money to protect consumers when prices are high. In the second part, the paper analyzes what are the news in the new offshore law, along with what has not been changed in the new law. Thus, the paper emphasizes that through this new law, Romania sends a message of trust and stability to investors and holders of oil agreements in the Black Sea, being ready to offer them the same long-term and very long-term conditions. The remaining of the paper analysis the main elements that may solve the offshore law vs. environmental protection debate for the main fear from this point of view, as certain environmental circles claim, is that Romania may not have a solid legislative framework in place to protect the environment in the event of major accidents in oil operations in the Black Sea. In the end, the results of this analysis reveal the growing importance of oil and gas sector in the economy. This comes at a time when global energy prices are at high levels, and Europe in particular is facing higher natural gas and electricity prices, largely amplified by the conflict in Ukraine.
Keywords: oil; natural gas; Black Sea; royalty; taxation; concession; European Union